Labial lipoblastoma in an infant: An uncommon tumor at an uncommon site - Raktim Mukherjee; Sanghamitra Bhattacharyya; Uttara Chatterjee (Wolters Kluwer Medknow Publications, 2023)
Lipoblastoma and lipoblastomatosis are benign fatty tumors of soft tissues that are unique to childhood. Occurrence of lipoblastoma in the labial region is infrequent and can cause diagnostic dilemma. Awareness about this entity is important to avoid hazardous treatment in young children. Here, we present a case of labial lipoblastoma in a 2-year-old child along with its differential diagnosis.